Rancang Bangun Sistem Informasi Berbasis Web Sebagai Panduan dan Rekam Data Nutrisi Ibu Hamil - Irfan Ardiansah; Mira Trisyani Koeryaman (Jurnal Ilmiah KOMPUTASI, 2018)
In West Java anemia is one of the most frequent contribution causes of maternal mortality and poor perinatal outcome also common preventable of postpartum bleeding, prematurity and low birth weight. The leading causes of anemia during pregnancy involve deficiency of nutrients essentials. Based on the current condition, it is essential to design health information system that provide advice on nutritional intake and recording data on food consumption of pregnant women. The research used engineering method with quantitative analysis approach to develop web application prototype. The analysis and design of the application use Waterfall method, which the structure of application development can be traced from the analysis process until the maintenance process. The testing process is used to make sure the application developed is high-quality, so it will perform its function correctly without inflicting difficulty and applicable for users, in case if there are any errors in the system it will return to the implementation stage so that mistakes can be corrected. This application is expected to help improve the quality of life of pregnant women so that the incidence of death of pregnant women and infants in West Java has decreased.